Advancing Diversity and Inclusion in United States' Space Weather and Space Physics Communities - J. L. Gannon; Noé Lugaz (Space Weather)
Abstract Following a panel discussion at the 2019 AGU Fall Meeting with an atypical gender ratio, we discuss the diversity and inclusion (D&I) initiatives at NASA Goddard Space Flight Center with Deputy Director for the Heliophysics Science Division, Dr. Antti Pulkkinen. We focus on gender diversity and efforts by AGU to promote D&I and how it applies specifically to the Space Physics and Aeronomy (SPA) section of AGU.